Defining the potential role of the mineralocorticoid receptor in musculoskeletal health and bone crosstalk with other tissues - Husam Bensreti; Joseph C. Shaver; Christopher L. Yearwood; Dima W. Alhamad; Eric C. Morey; Shabiha Sultana; Mark W. Hamrick; Kate Kosmac; Wendy B. Bollag; Eric J. Belin de Chantemele; Carlos M. Isales; Meghan E. McGee-Lawrence (Journal of Endocrinology, 2026)
Abstract Excessive mineralocorticoid receptor (MR) activation in the heart and vasculature leads to pathological effects such as extracellular matrix accumulation, oxidative stress, and sustained inflammation. While MR’s role in cardiovascular and renal systems is well understood, MR signaling has also been implicated as a key driver of homeostasis and pathological changes in several other body systems including skeletal muscle and adipose tissue. The glucocorticoid receptor (GR) and MR are structurally and functionally linked, sharing 95% similarity in DNA binding domains and recognizing many of the same hormone response elements (HRE) as transcriptional regulators of target genes. The role of GR in bone has been defined through several mechanistic studies, whereas the role of MR in bone is understudied. Because mineralocorticoid signaling regulates renal sodium and calcium handling, chronic hyperaldosteronism may indirectly disrupt skeletal homeostasis through urinary calcium wasting and secondary alterations in parathyroid hormone signaling. Furthermore, MR inhibition through MR antagonists (MRAs) has been associated with beneficial skeletal effects, particularly in settings of hyperaldosteronism and 11β-HSD2 deficiency. In this review, we present historical and current scientific findings on the role of genomic MR signaling in bone and extra-skeletal tissues that may be involved in crosstalk with the skeletal system. Furthermore, we also highlight the availability of tools to study MR signaling in the context of the musculoskeletal system.